Career Planning Analysis of Experience and Capability (Human Resource Management Literature Review) - Hermawan, Eric (Green Publisher, 2022)
The Literature Review article Career Planning Analysis of Experience and Capability is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Career planning affects experience; 2) Career Planning affects Ability; and 3) Experience influence ability. Apart from these exogenous variables that affect endogenous variables, there are other factors including the variables Performance, Motivation and Education.